PENGARUH MODERNISASI TERHADAP PERILAKU SISWA SEKOLAH DASAR - Andriyani, Yunita; Husein Arifin, Muh.; Wahyuningsih, Yona (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Modernization is an event that cannot be avoided by all countries in the world, especially Indonesia as a developing country. Modernization can occur in the world of education. Modernization is able to provide influence and impact on students if it is not monitored optimally by educators. The phenomenon of modernization can make elementary school students have an active, innovative and visionary mindset. But the phenomenon of modernization can also result in changes in the behavior of elementary school students, so it is feared that it will eliminate the noble character they have. This article discusses the impact and effects of modernization on the behavior of elementary school students. Furthermore, it will be discussed about the role of the teacher to minimize the negative impact of modernization which can endanger the character formation of elementary school students.